Influence of Bullying on the Quality of Life Perception of Chilean Students [Bullying y Calidad de Vida Relacionada Con la Salud en Adolescentes Escolares Chilenos] - Montano-Espinoza, R (Sociedad Medica de Santiago, 2015)
Background: Bullying has a negative impact on the perception of adolescents of their quality of life. Aim: To analyze the association between being bullied and health related quality of life in Chilean adolescents. Material and Methods: The bullying module of the KIDSCREEN 52 survey and the KIDSCREEN 10 survey to assess health related quality of life were applied to 7737 students aged 10 to 18 years. Social and demographic data, information about disability and type of school were also gathered. Results: Fifteen percent of surveyed students were bullied. A lower quality of life perception increased by a factor of 2.6 among bullied students. It also increased by a factor of 4.4 among students with a low self-esteem, by a factor of 3.1 among those who perceived their health status as regular or bad and by a factor of 1.4 among women. Conclusions: Bullying is associated with a lower quality of life perception among Chilean students. © 2015 Sociedad Medica de Santiago. All rights reserved.